(untitled) (Cadernos de Sociomuseologia, 2020)
In this work we approach the experience of the Los Cuchimilcos Museum. This was a work done with the directors, teachers and students of the Nuestra Señora del Buen Consejo School, located in the town of Breña (Lima, Peru). The purpose was to reopen a museum that existed in the place. Through three work stages, 15 participants between the ages of 11 and 14 jointly, playfully and dialogically carried out a museological and heritage process that resulted in the design and assembly of an archeology museum. In the process, we observed and understood other elements and dialogues in heritage and collective work, which led us to make significant considerations when working with culture, memory and the past. This work made us rethink and evaluate the ways on how the archaeological heritage is assumed and works; where most of the time adultcentrism prevails; as the best way to build knowledge and represent it museally. However, with the experience presented here, we observe that other ways of doing museology are also possible. Keywords: children’s museum; socio-museology; archeology; heritage.